Social context and noise affect within and between male song adjustments in a common passerine. (14th July 2020) - Grabarczyk, Erin E; Vonhof, Maarten J; Gill, Sharon A
Abstract: Across populations, animals that inhabit areas with high anthropogenic noise produce vocalizations that differ from those inhabiting less noisy environments. Such patterns may be due to individuals rapidly adjusting their songs in response to changing noise, but individual variation is seldom explored. Therefore, we tested the hypothesis that male house wrens ( Troglodytes aedon ) immediately adjust their songs according to changing noise and that social context further modifies responses. We recorded songs, quantified noise, and defined social context within pairs as female fertile status and between males as number of conspecific neighbors. We used a reaction-norm approach to compare song trait intercepts (between-male effects) and slopes (within-male effects) as a function of noise. Individuals immediately adjusted song duration in response to changing noise. How they achieved adjustments varied: some sang shorter and others longer songs with greater noise, and individuals varied in the extent to which they adjusted song duration. Variation in song duration could be affected by competition as between-male noise levels interacted with number of neighbors to affect syllable duration. Neither within- nor between-male noise effects were detected for frequency traits. Rather, males with fertile mates sang lower-frequency songs and increased peak frequency with more neighbors. Among males, social context but not noise affected song frequency, whereas temporal structure varied between and within individuals depending on noise and social factors. Not all males adjusted signals the same way in response to noise, and selection could favor different levels of variation according to noise. Abstract : In response to rapidly changing anthropogenic noise, individual songbirds may immediately adjust their songs. Song structure may be further modified by social context. Among male house wrens, social context but not noise affected song frequency, whereas song duration varied within and between individuals depending on noise and social factors. Not all males adjusted signals the same way in response to noise, and selection could favor different levels of song variation according to noise.